CRISPR/Cas9, a universal tool for genomic engineering - A. V. Smirnov; A. M. Yunusova; V. A. Lukyanchikova; N. R. Battulin (Вавиловский журнал генетики и селекции)
The CRISPR/Cas9 system was initially described as an element of archeal and bacterial immunity, but gained much attention recently for its outstanding ability to be programmed to target any genomic loci through a short 20-nucleotide sgRNA region. Here we review some modern applications of the CRISPR/Cas9 system. First, we describe the basic mechanism of the CRISPR/Cas9 DNA recognition and binding, focusing in particular on its off-target activity. The CRISPR/Cas9 off-target activity refers to a non-specific recognition of genomic sites that have partial homology with sgRNA, occasionally resulting in unwanted mutations throughout the genome. We also note some recent improvements for enhancing Cas9 specificity or adding new functions to the system. Since Cas9-related hype is mostly driven by its remarkable potential for gene therapy and genome engineering, the latest CRISPR/Cas9 applications in these areas are also covered in our review. For instance, the CRISPR/Cas9 was recently used to control HIV infection and to repair genetic abnormalities, such as Duchenne muscular dystrophy or retinitis pigmentosa, both in cell cultures and rodent models. A programmable nature of CRISPR/Cas9 facilitates the creation of transgenic organisms through sitespecific gene mutations, knock-ins or large chromosomal rearrangements (deletions, inversions and duplications). CRISPR/Cas9 proved to be especially useful in pronuclear microinjections of farm animals as well, having strong impact on biotechnology. In addition, we review Cas9-augmented genetic screens that allow an unbiased search for new genes and pathways involved in a plethora of biological aspects, owing to Cas9 efficiency and versatility. Finally, we argue that gene drivers based on CRISPR/ Cas9 represent a powerful tool to modify ecosystems in the nearest future.